2007
DOI: 10.1128/jvi.01957-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Influenza Virus-Specific Effector and Memory B-Cell Responses to Immunization of Children and Adults with Live Attenuated or Inactivated Influenza Virus Vaccines

Abstract: Cellular immune responses to influenza virus infection and influenza virus vaccination have not been rigorously characterized.We quantified the effector and memory B-cell responses in children and adults after administration of either live attenuated (LAIV) or inactivated (TIV) influenza virus vaccines and compared these to antibody responses. Peripheral blood mononuclear cells were collected at days 0, 7 to 12, and 27 to 42 after immunization of younger children (6 months to 4 years old), older children (5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
143
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 48 publications
21
143
7
1
Order By: Relevance
“…Moreover, in subjects immunized with MF59-H5N1 both cell-mediated and antibody responses are strongly boosted by a third dose given 5 months after priming, indicative of the induction of immunological memory. Of note, the frequency of H5N1-IgG MBC measured after 3 doses of MF59-adjuvanted vaccines is comparable to that observed after seasonal influenza vaccination (20,21).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, in subjects immunized with MF59-H5N1 both cell-mediated and antibody responses are strongly boosted by a third dose given 5 months after priming, indicative of the induction of immunological memory. Of note, the frequency of H5N1-IgG MBC measured after 3 doses of MF59-adjuvanted vaccines is comparable to that observed after seasonal influenza vaccination (20,21).…”
Section: Discussionsupporting
confidence: 64%
“…This could be also explained by the relatively modest sample size of our study. While we only evaluated one single time-point after vaccination, previous work has showed that a significant increase in blood MBC levels was observed between 27-42 days after influenza vaccination in healthy adults [40,44].…”
Section: Discussionmentioning
confidence: 99%
“…Microneutralization antibody titers were determined using minor modifications of a previously reported method [24,25]. Ten 2 fold dilutions of serum, starting at 1:10 and ending at 1:5120, were made in culture medium [modified Eagle's medium ( MEM) −1% BSA with Penicillin Streptomycin] and 50 µl of each dilution was mixed with 50 µl containing 50% Tissue Culture Infective Dose of the H1N1 A/New Caledonia/20/99 or H3N2 A/Wisconsin/67/2005 viruses.…”
Section: Influenza Microneutralization Assaymentioning
confidence: 99%